Hydro-Oceanographic Dynamics in the Rupat Utara Coastal Area - Ilham Ilahi; Mubarak Mubarak; Maellynia Mustofa; Novia M. Afianti (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2024)
Coastal areas are one of the areas that have very potential both functionally and economically as a source of life for the surrounding community. However, if the management of coastal resources does not have sustainability, various problems will arise. Rupat Island is one of the water areas that is a crossing path between countries. Sustainable management of coastal areas must follow planning, utilization, supervision, and control of the impact that will be caused both by humans in utilizing it and the effect of oceanographic phenomena on coastal areas, such as hydro-oceanographic factors. This research aims to analyze the characteristics and factors that cause coastal environmental degradation, as well as the ecological carrying capacity of coastal areas in terms of physical aspects of oceanography. The method used in this research is a survey method, which involves interviews and questionnaires analyzed qualitatively and quantitatively. Data collection was done using a purposive sampling method based on affordability. The resulting bathymetric contours indicate that the waters in the middle of the Malacca Strait have a high depth (40 m) with more inland areas (approaching Rupat Island), and the sea depth decreases. The tides shown are field and secondary tides obtained through the prediction of tidal data by NAOTide software. The results of the graph displayed are very appropriate, which shows that the tidal type of Rupat Utara is a mixed tide inclined to double daily (Mixed Tide Prevailling Semi-diurnal). Current patterns from low to high tide have the same direction, from the northeast towards the southeast, with the highest current velocity occurring in February and the current velocity value above 0.5 m/s. While at high tide towards low tide, the current pattern has the opposite direction, namely from the southeast to the northeast, with the highest current speed occurring in December and above 0.8 m/s. The IKP calculation of the entire research area of Tanjung Punak Village is the area with the highest vulnerability level value, with a GPA value of 1215, and the lowest vulnerability level value in Tanjung Medang Village, with a GPA value of 216. The phenomenon of coastal area damage in the Rupat Utara area is almost found in every observation location, which is caused by the impact of both hydro-oceanographic factors and anthropogenic factors.